Knockdown of insulin receptor substrate 1 reduces proliferation and downregulates Akt/mTOR and MAPK pathways in K562 cells - Machado-Neto, Joao Agostinho (2011)
BCR-ABL kinase activates downstream signaling pathways, including the PI3K-Akt/mTOR and the MAPK pathway. IRS1 has been previously described as constitutively phosphorylated and associated with BCR-ABL in K562 cells, suggesting that IRS1 has role in the BCR-ABL signaling pathways. in this study, we analyzed the effect of IRS1 silencing, by shRNA-lentiviral delivery, in K562 cells, a CML cell line that presents the BCR-ABL. IRS1 silencing decreased cell proliferation and colony formation in K562 cells, which correlates with the delay of these cells at the G0/G1 phase and a decrease in the S phase of the cell cycle. Furthermore, IRS1 silencing in K562 cells resulted in a decrease of Akt, P70S6K and ERK1/2 phosphorylation. Nevertheless, apoptosis was unaffected by IRS1 knockdown and no alterations were found in the phosphorylation of BAD and in the expression of BCL2 and BAX. BCR-ABL and CRKL phosphorylation levels remained unaffected upon IRS1 silencing, and no synergistic effect was observed with imatinib treatment and IRS1 knockdown, indicating that IRS1 is downstream from BCR-ABL in conclusion, we demonstrated that inhibition of IRS1 is capable of inducing the downregulation of Akt/mTOR and MAPK pathways and further decreasing proliferation, and clonogenicity and induces to cell cycle delay at G0/G1 phase in BCR-ABL cells. (C) 2011 Elsevier B.V. All rights reserved.